Agricultural Risk and Crop Insurance in Orissa in a Globalised Economy. - Swain, Mamata (2008)
A critical evaluation of the area yield crop insurance scheme implemented in the state of Orissa reveals that it has several flaws and there is a need to redesign it as crop insurance scheme to increase the breadth of coverage, improve the operational efficiency and enhance financial performance. Rainfall insurance is a better alternative due to less administrative cost, transparency and mitigation of moral hazard problem representing exaggerated amount of relief sought against actual loss. Public sector may address catastrophic risk and provide multi-peril insurance with subsidy, but private sector should be allowed to provide insurance products for less severe events and for individual, independent and localised risk. Simultaneously, micro-insurance, that is insurance for the poor, should be encouraged through participation of banks, non-governmental organisations and microfinance institutions. In the era of liberalisation and globalisation, due to removal of trade barriers and integration of domestic market with world food market, the food prices have become notoriously volatile. Under such a situation, new initiatives like farm income insurance schemes are necessary to insure both production and price risks.